TINJAUAN YURIDIS TERHADAP PENANGKAPAN DAN PENAHANAN ABU BAKAR BA'ASYIR MENURUT KUHAP - Asrianto Zainal (Institut Agama Islam Negeri Kendari, 2013)
Abstract: This writing attends to know and how tofind the legal problem solving which cases in Law ofCrimminal Procedur Book (KUHAP) espicially legalor illegal underrating based on indictment of AbuBakar Ba’asyir. To analyze the implementation basedon due process law, that’s make some cases how tosolve the problem among people. That due process lawdirected a point find a legal problem solving which inlegal or illegal process. In other words, that is the dueprocess law producing by KUHAP was to be executedor not, second, is the rights of arrester can be legal orillegal execution in with producing by KUHAP, untilthose each of persons were filed the human raights asbecame as freedom. The other think that to analyzedthe nornms and rules with in due process law above alegal or illegal underrating on Abu Bakar Ba’asyir.To process the extra court is the rights for every one.That the suspect or the accused men can be dependedtheir rights form his accusation by rules. In the chapter77 KUHAP was ruled which in limitative abovecompetence of extra court to investigated and to makedecision are. The first to investigate the arrest legal orillegally process and to end discontinuance ofinvestigation and indictment. Second, to ask thecompensation/indemnity rehabilitation relating with thelegal or illegally process and to end discontinuance ofinvestigation and indictment.Keywords: Legal or illegal process